Nutritional status of women with gestational hypertension compared with normal pregnant women. (May 2013) - Kazemian, Elham; Dorosty-Motlagh, Ahmad-Reza; Sotoudeh, Gity; Eshraghian, Mohammad-Reza; Ansary, Samaneh; Omidian, Mahsa
<x xml:space="preserve">Abstract</x> Background: Some evidence indicated the role of nutrition in the development of hypertensive disorders of pregnancy. Methods: This case–control study was conducted on 113 women with gestational hypertension and 150 healthy pregnant women referred to Shahid Akbarabadi Hospital in Tehran. A demographic questionnaire was filled out for all participants. A validated semi-quantitative food frequency questionnaire was used to assess the dietary intakes of the study subjects. All nutrients were adjusted for total energy intake. Logistic regression was used to find the association of energy and nutrient intakes with gestational hypertension. Results: We found that higher intakes of energy (OR, 1.33; 95% CI: 1.17–1.52), monounsaturated fatty acids (OR, 1.34; 95% CI: 1.03–1.74) and polyunsaturated fatty acids (OR, 1.26; 95% CI: 1.00–1.54) were positively associated with the risk of gestational hypertension after adjustment for confounders. We also observed decreased odds of gestational hypertension with increased intakes of vitamin C (OR, 0.87; 95% CI: 0.81–0.94), potassium (OR, 0.45; 95% CI: 0.28–0.71) and magnesium (OR, 0.68; 95% CI: 0.51–0.89). Conclusion: This study demonstrates higher intakes of energy, monounsaturated fatty acids and polyunsaturated fatty acids as well as lower intakes of vitamin C, potassium and magnesium are positively correlated with the risk of developing gestational hypertension.